Surgery In Infective Endocarditis - Abood, Laith S. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Early surgery during the active phase of infective endocarditis was considered to carry high morbidity and mortality due to technical difficulties on an inflamed tissues. Objectives: Is to focus a light on the increasing indications for surgery during the active phase of infective endocarditis which lead to significant drop in the hospital mortality. Patients and Methods: Eighteen patients with bacterial endocarditis and valvular dysfunction were admitted to Iraqi center for heart diseases during the period from January 2008 –April 2013. All of them were fully investigated and adequately prepared for open heart surgery. Result: Seven-teen patients were successfully treated surgically with uneventful post-operative course. One patient developed another attack of prosthetic valve endocarditis which mandates a redo surgery .Only one patients died two years later. Conclusion: The indications for surgery and its timing are difficult decisions to take . Close follow up , collaboration between cardiologist cardiac surgeon and laboratory personnels are mandatory.